Waqf Forest Development Strategy in Cibunian Bogor - Asep Nurimam Munandar; Mukhaer Pakkana; Amrizal Amrizal (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
Indonesia has a significant waqf potential. However, its realization has not been optimal. Using the Bogor Waqf Forest Foundation as the case study, this research analyzes the implementation of the waqf forest development strategy. It assesses the priority Benefits, Opportunities, Costs, and Risks (BOCR) faced. This study uses the business model canvas (BMC) to the BOCR by mapping the nine business blocks of the canvas model. The study finds that the main priorities to strengthen the management and development of the forest waqf project are 1) nāẓir professionalism and competence in knowledge of waqf laws, 2) research and discourse development, and 3) personal approach to collecting waqf funds.